A modified numerical model for predicting carbonation depth of concrete with stress damage. (18th October 2021) - Shi, Xinyu; Yao, Yan; Wang, Ling; Zhang, Cheng; Ahmad, Iftikhar
Highlights: A modified numerical carbonation model was proposed based on the damage theory. The parameters were adjusted by the inverse method to fit the test results. Two pieces of FEM software jointly simulated carbonation of damaged concrete. The carbonation behavior of stress-damaged concrete in mesoscale was analyzed. Abstract: A modified carbonation model centered on humidity-temperature-CO2 coupling was proposed. Its parameters were determined based on a 3-year natural carbonation test. The model was then verified by comparing carbonation results with that of accelerated experiment (2% and 20% CO2 ) and other publications. The effect of coarse aggregate, crack, and carbonation direction was investigated for undamaged concrete. The influence of stress damage (calculated by ABAQUS) and evaluating method was investigated for stress damaged concrete. The results indicated that the proposed model put more weight on the stress damage. It predicted the service life decreases to 1/3 of undamaged concrete for the example in this article.